B cell receptor inhibition as a target for CLL therapy. Issue 1 (March 2016) - Jeyakumar, Deepa; O'Brien, Susan
Abstract: Inhibitors of the B cell receptor (BCR) represent an attractive therapeutic option for patients with chronic lymphocytic leukemia. Recently approved inhibitors of Bruton's tyrosine kinase (ibrutinib) and phosphatidylinositol 3-kinase (idelalisib), are promising agents because they are generally well tolerated and highly effective. These agents may be particularly important in the treatment of older patients who are less able to tolerate the myelosuppression (and infections) associated with chemoimmunotherapy. As a class of medications, BCR inhibitors have some unique side effects including redistribution lymphocytosis. Ibrutinib has specific toxicities including increased risk for bleeding and atrial fibrillation. Idelalisib also has some unique toxicities consisting of transaminitis, diarrhea and pneumonitis. Ongoing clinical trials are evaluating these agents in combination with antibodies, chemotherapy and other small molecules.